2013
DOI: 10.3126/jpn.v3i6.8988
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fine needle aspiration cytology in diagnosis of thyroid swelling

Abstract: Accuracy of fine needle aspiration cytology in diagnosis of thyroid swelling. Keywords:Fine needle aspiration cytology; Thyroid lesions; Histopathology. Correspondence:Dr. Suspana Hirachand, MD Department of Pathology, Kathmandu Medical College and TeachingHospital, Kathmandu, Nepal Email: suspi1974@hotmail.com Background: Fine needle aspiration cytology has been shown to be simple, safe, cost effective and quick to perform procedure with excellent patient compliance. It is a well established technique fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
6
12
1
Order By: Relevance
“…Most common age group affected in our study was 41-50 years followed by 31-40 years. Our study is consistent with the studies done by Yassa et al Females outnumbered males with female to male ratio was found to be 16.9:1 which is comparable to studies done by Hirachand S et al 12 Colloid goiter is the most common diagnosis encountered in our study (53%) which is similar to studies of Jain D et al 6 De Quervains Thyroiditis is the third most common diagnosis, the diagnostic picture of multinucleate giant cells, granulomas may also be seen in Hashimoto's thyroiditis and thus differentiation may be difficult. One differentiating point is lymphocytic impingement which is seen in Hashimoto's but not in De Quervain's thyroiditis, only one case of Graves disease was reported and it is the least common diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Most common age group affected in our study was 41-50 years followed by 31-40 years. Our study is consistent with the studies done by Yassa et al Females outnumbered males with female to male ratio was found to be 16.9:1 which is comparable to studies done by Hirachand S et al 12 Colloid goiter is the most common diagnosis encountered in our study (53%) which is similar to studies of Jain D et al 6 De Quervains Thyroiditis is the third most common diagnosis, the diagnostic picture of multinucleate giant cells, granulomas may also be seen in Hashimoto's thyroiditis and thus differentiation may be difficult. One differentiating point is lymphocytic impingement which is seen in Hashimoto's but not in De Quervain's thyroiditis, only one case of Graves disease was reported and it is the least common diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…11 Also, Hirachand et al, found in their study that the most common lesion in the thyroid gland was colloid goiter. 12 Among the malignant neoplasms the commonest was papillary carcinoma which coincides with our results.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to findings observed in studies conducted by Sinna and Ezzat, Kasper et al ., and Hirachand et al . [ 1 2 3 ] In a study conducted by Carvalho et al ., they found that FNAC and FNNAC provided similar cytological diagnosis, respectively (malignant: 3.8% vs. 3.8%, P = 0.871; suspicious: 10.4% vs. 10.8%, P = 0.913; and nondiagnostic: 10.0% vs. 11.2%, P = 0.598). [ 5 ] However, as in our study, the follicular neoplasm and nondiagnostic cases were more in nonaspiration cytology than in aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Hirachand et al ., the nondiagnostic smears were more (2.6%) in FNAC, but the percentage of colloid goiter (72.53%) and papillary carcinoma (4.76%) was similar to this study. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation